SOCIO-ECONOMIC AND ECOLOGICAL IMPACT OF MALARIA – A CASE STUDY OF NEEMUCH, MADHYA PRADESH - Sewak, Sadhana (International Journal of Research -GRANTHAALAYAH, 2015)
Malaria is one of the oldest chronic, most dreaded killer diseases. It is a protozoan Plasmodium borne disease which is transmitted in humans by very efficient mosquito Anopheles. Out of four plasmodium genus, vivax is more dominant and falciparum species likely to cause severe lethal malaria.According to WHO, malaria killed 627000 people in 2012, majority of them sub-Saharan African children under the age of 5. This preeminent tropical parasite disease is one of the top 3 killers among communicable diseases. It is the only vector borne disease to be placed on WHO- DALY’s (disability adjusted life years) list, as it affects the mortality and morbidity rate as well as economy of any country.